Tensions and connections between social work and anti-capitalist disability activism: disability rights, disability justice, and implications for practice - Eiler, Elijah C.; D'Angelo, Karen (Journal of Community Practice, 2020)
Social work’s relationship to disability activism under capitalism is an underexplored area of the profession’s literature. This paper aims to help address this gap by providing a conceptual discussion of the tensions within disability activism, within social work, and between the two. Lenin’s analysis of the state is used to integrate opposing ideologies. We begin by providing a historical overview of the disability rights and disability justice movements along with recommendations for an integrated approach. We then connect ideological trends within social work to these models. We end with implications for social work practice with disabled people and suggested research. © 2020 Taylor & Francis Group, LLC.
5 citations (Crossref) [2023-10-31] WOS:000592552800001
Keywords: Lenin; Radical social work; anarchism; dept.swk; disability justice; disability rights; mutual aid; peer-reviewed

Self-Concept Among Formerly Incarcerated Sexual Minority Women - Stone, Al; Smoyer, Amy; D’Angelo, Karen (Social Sciences, 2025)
Sexual minority women (SMW) are a resilient yet vulnerable population who may experience poor psychosocial outcomes due to minority stress associated with their marginalized status and traumatic experiences resulting from interpersonal and structural violence. When SMW are incarcerated, the trauma of this experience can exacerbate existing mental health challenges. Self-concept is a key measure of mental health that is associated with increased self-efficacy and positive psychosocial outcomes. This analysis explores the ways in which incarceration impacts the self-concept of SMW. Secondary data analysis of three qualitative interviews with formerly incarcerated SMW was conducted. Specifically, Gilligan’s Listening Guide was used to create “I poems” that articulate the participants’ narratives and contrapuntal voices. These poems were then analyzed to build knowledge about participants’ self-concept. This analysis informs our understandings of self-concept among SMW, violence against women, the vulnerability of binary constructs, and the ways in which people negotiate past, present and future selves. The findings can inform interventions that seek to mitigate the psychosocial risks faced by SMW and formerly incarcerated people and improve outcomes for these populations.
Keywords: Clinical psychology; Developmental psychology; LGBT; Listening Guide; Psychology; Sexual minority; Sexual orientation; Social psychology; dept.swk; incarceration; lesbian; qualitative; self-concept; sexual minority women; transgender

Building or Burning: Critical Reflections on Social and Political Change - Krings, Amy; D’Angelo, Karen; Ivery, Jan M.; Murphy-Nugen, Amy B. (Journal of Policy Practice and Research, 2023)
Num Pages: 6
Keywords: dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: White supremacy; dept.swk; peer-reviewed

Advancing health equity: an innovative program for building community engagement in research - Santilli, Alycia; LaMonaca, Katherine; Carr, Kendra; Rue, Bailee; D'Angelo, Karen; Higginbottom, Jackson; Morales, Sofia; Taylor, Marquita A.; Vicente, Genesis A.; Lin-Schweitzer, Anna; Duffany, Kathleen O'Connor (Progress in Community Health Partnerships: Research, Education, and Action, 2023)
Background: The Community Research Fellows (CRF) program seeks to mobilize New Haven residents with lower incomes or from communities of color who are educated and equipped to engage as equal partners in health research at Yale University. The training program combines curriculum-based information with 'on-the-ground' experience with Yale research projects, while building relationships between CRFs and researchers. The Community Alliance for Research and Engagement launched two consecutive cohorts of the program in 2018–2020., Objectives: To assess the effect of the CRF program on participants' knowledge of the research process and confidence to engage in research and participants' satisfaction and perspectives on the program., Methods: The evaluation of the CRF program included four components: 1) Pre- and Post- Program Surveys to assess change in confidence and self-reported knowledge. 2) Curriculum Feedback Satisfaction Survey to gauge satisfaction and make program improvements after each training session. 3) Post-Program CRF Interviews to explore their CRF experiences. 4) Research Team Surveys to assess program satisfaction and areas for improvement., Results: CRFs reported increased confidence and knowledge, personal and professional growth, and interest in community-engaged research. Overall, participants were very satisfied with each training module., Conclusions: The CRF program demonstrated that community members are well-suited, well-positioned, and eager to engage in and inform public health research. CRFs bring capacity and valuable perspective to research teams. The CRF training program offers an innovative approach to address power imbalances in research and to move towards more equitable community–university partnerships for improved health outcomes.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed